Peran Peran Kepolisian Dalam Penyelesaian Konflik Antar Pencak Silat Melalui Restorative Justice di Kecamatan Patrang Kabupaten Jember - Oeny Angga Mahendra; Diyan Isnaeni; Moh. Muhibbin (Fakultas Hukum Universitas Islam Jember, 2025)
Communal violence involving martial arts schools has become a recurrent issue that threatens local social stability. This study examines the role of the police in resolving conflicts between martial arts schools through a Restorative Justice (RJ) approach in Patrang District, Jember Regency, and identifies the factors influencing the effectiveness of its implementation. Using an empirical juridical research method, data were collected through document analysis (LPM, SP.Gas, SP.Lidik, and Mediation Reports) and interviews with police investigators and leaders of martial arts organizations. The findings reveal that the police perform multiple roles, including pre-emptive and preventive measures, the facilitation of penal mediation, and the application of proportional repressive actions based on legal discretion under Police Regulation No. 8 of 2021. The effectiveness of RJ is shaped by three key factors: procedural validity, social legitimacy of the police and willingness of conflicting groups to reconcile, and institutional support from the Jember Martial Arts Communication Forum (FKPJ) as a multiparty dialogue platform. Although RJ successfully suppresses escalation and prevents retaliation, its implementation faces challenges such as personnel limitations, internal group dynamics, and maintaining neutrality.